1988
DOI: 10.1111/j.1471-4159.1988.tb04867.x
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide Portion of GM1 Enhances Process Formation by S20Y Neuroblastoma Cells

Abstract: The oligosaccharide portion of ganglioside GM1 was found to enhance neuritogenesis by S20Y murine neuroblastoma cells grown in vitro. The average length of the neurites produced by cells grown in the presence of the oligosaccharide portion of GM1 was comparable to that of cells grown in the presence of intact GM1. The processes of these cells were significantly longer (p less than 0.005, pooled t test) than those of cells grown in the presence of comparable concentrations of sialic acid, lactose, sialyllactose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…60). However, the enhancement of neuritogenesis and cell adherence by the sugar portion of GM 1 has been tentatively ascribed to the presence of a 71-kDa membrane protein in the case of murine cholinergic S20Y neuroblastoma cells (61)(62)(63). Based on the application of the GM 1 -neoganglioprotein and the binding of cells to surfaceimmobilized GM 1 in the absence and presence of galectin-1-specific antibody, as well as the total number of immunologically assessed galectin-1 molecules and glycocytochemically quantitated neoganglioprotein-binding sites, it appears reasonable to conclude that the murine and the human lines differ in their GM 1 receptors.…”
Section: ϫ9mentioning
confidence: 99%
“…60). However, the enhancement of neuritogenesis and cell adherence by the sugar portion of GM 1 has been tentatively ascribed to the presence of a 71-kDa membrane protein in the case of murine cholinergic S20Y neuroblastoma cells (61)(62)(63). Based on the application of the GM 1 -neoganglioprotein and the binding of cells to surfaceimmobilized GM 1 in the absence and presence of galectin-1-specific antibody, as well as the total number of immunologically assessed galectin-1 molecules and glycocytochemically quantitated neoganglioprotein-binding sites, it appears reasonable to conclude that the murine and the human lines differ in their GM 1 receptors.…”
Section: ϫ9mentioning
confidence: 99%
“…Based on our previous observations (Schengrund and Prouty, 1988;Fueshko and Schengrund, 1990), we hypothesized that GM 1 -binding proteins were present on the surface of S20Y cells. For morphological studies, the aminated oligo-GM 1 was conjugated to iminobiotin, and its interaction with S20Y cells visualized using a streptavidin-alkaline phosphatase complex.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have indicated that the ceramide portion of gangliosides is not essential for all functional interactions. In at least two instances, the addition of the free oligosaccharide moiety to neuroblastoma cells was found to evoke a similar neuritogenic response (Nakajima et al, 1986;Schengrund and Prouty, 1988). Ceramide is not recognized as part of the ligand per se by the toxin.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the oligosaccharide portion of GM| could stimulate neuritogenesis by S20Y murine neuroblastoma cells [49] suggested that molecules able to recognize the oligosaccharide portion o f GM| (oIigo-GM|) Recently a glycosidase, sialidase (neur aminidase, N-acetylneuraminosyl glycohydrolase, EC 3.2.1.18), associated with myelin, was postulated to function in the formation Fig. 1.…”
Section: Evidence For Cell Surface Ganglioside-binding Moleculesmentioning
confidence: 99%
“…Addition of the oligosaccharide portion of GQib to GOTO and NB-1 human neuroblastoma cells main tained in vitro resulted in enhanced process formation [20]. Similarly, the oligosaccharide portion of GM) was found to enhance neuritogenesis by S20Y murine neuroblastoma cells [49]. These observations suggest that the morphological changes resulted from the oli gosaccharide portion of the ganglioside inter acting with a cell surface component, since it is unlikely that the free, negatively charged, oligosaccharides could readily cross the plas ma membrane.…”
mentioning
confidence: 99%